2014
DOI: 10.1155/2014/560790
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Rapamycin and Torin/KU63794 in Inflammatory Response of 264.7 RAW Macrophages Stimulated by CA-MRSA

Abstract: Background. Rapamycin suppresses the RAW264.7 macrophage mediated inflammatory response but in lower doses induces it. In the present study, we tested the suppression of the inflammatory response in the presence of mTOR 1 and 2 inhibitors, Torin and KU63794. Methods. RAW264.7 cells were stimulated for 18 hrs with 106 to 107 CFU/mL inocula of community-acquired- (CA-) MRSA isolate, USA400 strain MW2, in the presence of Vancomycin. Then, in sequential experiments, we added Torin, KU63794, and Rapamycin alone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The mTORC links with other proteins and serves as a core component of two distinct protein complexes, mTORC-1 and mTORC-2, which regulate different cellular processes (34). The role of mTORC complexes was investigated by using the chemical inhibitors rapamycin, which inhibits mTORC-1, and torin, which inhibits both complexes (35,36). Because ribosomal p70S6 kinase is a downstream target of the mTORC-1 complex (34), we also investigated the role of p70S6K in the SM-induced cell death.…”
Section: Sm-induced Cell Death During Differentiation Into M1 Macroph...mentioning
confidence: 99%
“…The mTORC links with other proteins and serves as a core component of two distinct protein complexes, mTORC-1 and mTORC-2, which regulate different cellular processes (34). The role of mTORC complexes was investigated by using the chemical inhibitors rapamycin, which inhibits mTORC-1, and torin, which inhibits both complexes (35,36). Because ribosomal p70S6 kinase is a downstream target of the mTORC-1 complex (34), we also investigated the role of p70S6K in the SM-induced cell death.…”
Section: Sm-induced Cell Death During Differentiation Into M1 Macroph...mentioning
confidence: 99%
“…After 3 d of differentiation in response to the biomaterial, the medium was removed and replaced with medium containing 1 or 10 ng ml −1 rapamycin (R&D Systems), or 10 −8 or 10 −7 M dexamethasone (Sigma-Aldrich), or 0.5 or 5 μM pravastatin (Sigma-Aldrich), or 0.1 or 1 μM celecoxib (Sigma-Aldrich). Concentrations were chosen based on literature [26,28,38,39] and previous work in whichmacrophages cultured in monolayers were treated with these medications [23]. Dimethyl sulfoxide (DMSO) was used as avehicle for dexamethasone and rapamycin and the final DMSO concentration in the cultures was <0.01%.…”
Section: Modulation Of Macrophages Adhering To Biomaterialsmentioning
confidence: 99%
“…Rapamycin was found to exhibit a significant induction-suppression biphasic response, whereas mTORC1/2 inhibitors did not exhibit induction and cytokine production was suppressed 50%-60%. 131 Similarly, another recent study has shown that mTORC1/2 inhibition can inhibit inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells. 132 The differential effect of different mTOR inhibitors on inflammatory response could indirectly have an effect on tumor response.…”
mentioning
confidence: 92%